Segmental specializations in the Malpighian tubules of the fire ant Solenopsis saevissima Forel 1904 (Myrmicinae): an electron microscopical study - Arab, A.; Caetano, F. H. (Elsevier B.V., 2002)
The Malpighian tubules of workers of the fire ant Solenopsis saevissima (Myrmicinae) were analyzed by scanning and transmission electron microscopy in order to determine their functional organization and association with the hindgut epithelium. The ants showed six Malpighian tubules with three segments morphologically and structurally different. The proximal segment was long and its cells showed abundant smooth endoplasmic reticulum and lipid droplets, which suggest their role in lipid secretion. The mid segment was long and undulated and it was composed by the cells that showed the typical features of ion transporting epithelia. The distal segment, short and flattened, adheres to the rectum wall. The cells of this segment showed the basal lamina fused to that of the rectum, it is probable that this part of the tubule may play a role in ion and water uptake from the feces. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: ant; excretion; ion uptaking; Malpighian tubules; rectum